A secure communication over wireless sensor devices using intelligent arrival estimation algorithm. (2018) - Ananthi, J. Vijitha; Koresh, H. James Deva; Vengatesan, S.; Glorita, Y. Blessina Anet
The major challenge in wireless sensor network is used to maintain the successful and secure communication between two different devices with lifetime enhancement. Without security communication, sensor network will spoil the overall network resources. To avoid such type of an issue, we proposed a new enhancement scheme called 'intelligent arrival estimation (IAE)', by using this scheme nodes can be successfully performing the communication from one region to the other region without any interruption. We introduced cluster head and global cluster head in sensor network, which cluster head is responsible for carry over the communication between different regions and global cluster heads. Global cluster will act as gateway between the different regions as well as which is used to maintain the node details present in different cluster regions.